Key Factors For Peer-To-Peer Accommodation Adoption Among Tourists In Idanre Hills: A Sustainable Approach In The Sharing Economy - Adetola, B. O.; Adekitan, K. G. (Journal of Science, Technology and Innovation Research, 2025)
Peer-to-Peer (P2P) accommodation services offer transformative potential for the hospitality and tourism industry by creating new services with improved processes for the suppliers and additional values for the tourists. However, the potentials of P2P accommodation in Nigeria's tourism sector are yet to be realized. This study therefore investigated tourists’ motives and willingness to use Peer-to-Peer accommodation in Idanre community, Ondo State, Nigeria. Data was collected by administration of a well-structured questionnaire to 100 tourists purposively sampled in the study location. The data obtained were analyzed with both descriptive (percentages, charts, means, standard deviation) and inferential statistics (correlation and T-test). Findings from the study revealed that majority of the respondents at Idanre Hills were male 60%, within ages between 18- 45 years, visited with their families on holidays and were all Nigerians. Highest percentage (51%) of the tourists were first time visitors to Idanre Hill. Although awareness about Peer-to-Peer accommodation was very low amongst the respondents (84%), majority (64%) of the tourists were willing to adopt and use peer-to-peer accommodation. Moreover, the tourists were driven and motivated to use peer-to-peer accommodation largely because of two factors grouped as social motive (mean=4.06) and economic motive (mean=4.02). Provision of adequate safety measures by the host community for tourists, availability of peer-to-peer accommodation facilities in the community and possibility for host and tourists to share lifestyle that promote friendliness had the highest mean amongst the social motives while economic appeal of peer-to-peer accommodation services offering lower cost compared to conventional hotels and enhancement of local economy through peer-to-peer accommodation platform as a more sustainable business model were highest amongst the economic motives. However, the economic and social motivation factors for using peer-to-peer accommodation were not significantly different (p>0.05). The key factors identified in this study could be harnessed and used for effective management decisions and policy formulation for sustainable development of tourist destinations in Nigeria.